Aklimatization Black Orchid Plantlets (Coelogyne pandurata Lindl.) with Biostimulant Moringa Leaf Extract (Moringa oleifera Lamk.) - Rina Karmila; Zulfa Zakiah; Mukarlina (Jurnal Biologi Tropis, 2022)
The growth of black orchid plantlets (Coelogyne pandurata Lindl.) are slow at the acclimatization stage. An alternative was used moringa leaf extract (Moringa oleifera Lamk.) as a biostimulant. The aim of this research to find out the effect of giving moringa leaf extract on the growth of black orchid plantlets at the acclimatization stage and to obtain the best concentration and timing of extract to increase the growth of black orchid plantlets. The research used a factorial completely randomized design (FCRD) method with two factors. Factor I is the concentration of the extract which consists of 5 levels, namely 0, 25, 50, 75 and 100 mg/L. Factor II is the application time which consists of 2 levels, namely once a week and every 2 weeks, each treatment is repeated 5 times. The results showed that moringa leaf extract had a significant effect on the mean leaf width and number of plantlet roots of black orchids. Extract concentration of 50 mg/L was the best concentration on the growth of black orchid plantlets with an average leaf width of 0.76 cm and an average root number of 8.2. Recommended for the acclimatization of black orchids to use extract concentration 50 mg/L.